Outcomes research on children with medical complexity: A scoping review of gaps and opportunities. (11th December 2019) - Looman, Wendy S.; Park, Young Shin; Gallagher, Tiffany T.; Weinfurter, Elizabeth V.
Abstract: Background: There has been a recent, rapid increase in the number of studies of children with medical complexity (CMC) and their families. There is a need for attention to gaps and patterns in this emerging field of study. Objectives: The purpose of this scoping review was to identify patterns and gaps in the evidence related to classification systems, data, and outcomes in studies of CMC. Data Sources: We searched peer‐reviewed journals for reports of quantitative studies focused on CMC outcomes published between 2008 and 2018. On the basis of a structured screening process, we selected 63 reports that met our inclusion criteria. Study Appraisal and Synthesis: We used the methodological framework for scoping studies described by Arskey and O'Malley to map relevant literature in the field and the ECHO model to categorize studies according to three health outcome domains (economic, clinical, and humanistic). Results: The terminology used to describe and classify CMC differed across studies depending on outcome domain. Two thirds of the reports focused on economic outcomes; fewer than a quarter included child or family quality of life as an outcome. A majority of studies used a single source of data, with robust analyses of administrative, payer, and publicly available data. Conclusions and Implications of Key Findings: Research on CMC and their families would benefit from standardization of terms and classification systems, the use of measurement strategies that map humanistic outcomes as trajectories, and more attention to outcomes identified as most meaningful to CMC and their families.